An Unusual Case: Salmonella UTI and Orchitis in HIV Patient - Sabrina Arshed; Hongxiu Luo; John Middleton; Abdalla Yousif (Case Reports in Medicine)
Salmonellosis is a major cause of gastroenteritis in the United States; however, nontyphoidal strains of Salmonella have also been known to cause urinary tract infections, usually transmitted via the fecal-urethral route. This can lead to critical illness in those patients with immune deficiencies, especially HIV, cancer patients, and those with diabetes mellitus. However, the spread of the infection from the urinary tract to involve the testicles and epididymis is very rare. Here, we present the first documented case of an immune-compromised young male with a urinary tract infection with orchitoepididymitis.